1983
DOI: 10.1021/bi00281a009
|View full text |Cite
|
Sign up to set email alerts
|

Chiral instability at sulfur of S-adenosylmethionine

Abstract: S-Adenosylmethionine, generated enzymically in chirally pure form (S configuration at sulfur), undergoes simultaneous irreversible conversion to 5'-deoxy-5'-(methylthio)adenosine and homoserine with a rate constant of 6 X 10(-6) s-1 at pH 7.5 and 37 degrees C and reversible conversion to an enzymically inactive stereoisomer (R configuration at sulfur) with a forward rate constant of 8 X 10(-6) s-1 at pH 7.5 and 37 degrees C. These forms of instability require small turnover times and/or stabilization through m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 29 publications
3
48
0
Order By: Relevance
“…This compound is derived from AdoMet metabolism in the polyamine biosynthetic pathway, and can also arise from nonenzymatic hydrolysis of AdoMet under physiologic conditions. 24 Hence, we evaluated the effect of MTA on OA-induced apoptosis. Pretreatment of hepatocytes with MTA abolished the apoptotic effect of OA (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This compound is derived from AdoMet metabolism in the polyamine biosynthetic pathway, and can also arise from nonenzymatic hydrolysis of AdoMet under physiologic conditions. 24 Hence, we evaluated the effect of MTA on OA-induced apoptosis. Pretreatment of hepatocytes with MTA abolished the apoptotic effect of OA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 Exogenous AdoMet can also undergo nonenzymatic hydrolysis in vivo into MTA and homoserine. 9,24 It has been suggested that the beneficial effects of AdoMet in liver damage could be attributed in part to its conversion to MTA. 9,10 Additionally, we have recently shown that MTA mimics AdoMet's effect on gene expression in cultured rat hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of DTB, AdoMet is bound to biotin synthase with low affinity [ Figure A major concern in assessing AdoMet binding by equilibrium dialysis is the instability of AdoMet toward both hydrolytic degradation and racemization at the chiral sulfonium (37). To minimize the effect of these processes on our binding results, we performed dialysis at 20 °C to slow racemization and used HPLC analysis to separate AdoMet from the various degradation products.…”
Section: Substratementioning
confidence: 99%
“…In this respect, it can be hypothesized that D-aspartyl-containing peptides could be methylated in vitro by PCMT using AdoMet, with opposite chirality at sulfur center (R), as methyl donor. Such an AdoMet enantiomer has been shown to be present in living cells [35].…”
Section: Discussionmentioning
confidence: 99%